Free‐living, continuous hypo‐hydration, and cardiovascular response to exercise in a heated environment. Issue 8 (24th April 2018) - Early, Kate S.; Earnest, Conrad P.; Theall, Bailey; Lemoine, Nathan P.; Harrell, Brian; Johannsen, Neil M.
Abstract: Chronic dehydration (DEH) and heat stress combined with poor cardiovascular (CV) health may influence physiological responses to exercise. We examined the effects of free‐living induced hypo‐hydration on physiological responses to exercise in a heated environment and whether resting CV health is related to these changes. Participants ( N  = 16, 20.6 ± 1.2 years) were randomized to 3 days of voluntary fluid restriction (DEH) or intake (hydration [HYD]) followed by an exercise bout. CV health was assessed by flow‐mediated dilation (FMD), pulse wave analysis, and heart rate variability (HRV). HYD was assessed by weight, urine color, and specific gravity (USG). Exercise trials were conducted in a heated environment (30.3 ± 0.8°C, 27.4 ± 7.4% RH) on a cycle ergometer for 30 min. Heart rate (HR), weighted skin ( T sk ) and mean body temperature ( T b ) and skin blood flow (SBF) were assessed during exercise. Pre‐exercise weight ( P  < 0.005), urine color, and USG ( P  < 0.001) were different in between trials. HR was greater in DEH (153 ± 26 bpm) versus HYD (144 ± 23 bpm, P  = 0.02) after exercise. No group differences were found, but a time interaction P  < 0.001) for all temperature responses and time‐by‐trial interaction for T re ( P  < 0.01) and T sk ( P  < 0.001) was observed. Greater changes in T re ( P  = 0.02) and T sk ( P  < 0.01) were associated with increased FMD. Free‐living, continuous DEH alters weight, blood, and urine markers of HYD as well as HR response during exercise. Resting CV health was related to increased change in T re and T sk, suggesting CV health plays a role in the mechanism of heat dissipation when DEH even in college‐age men and women. Abstract : Free‐living hypohydration and cardiovascular (CV) health may alter thermoregulation. This study suggests chronic hypohydration in overtly adults influences markers of hydration. In addition, CV health may play a role in dissipating heat.